Genome-wide analysis and expression profiling under heat and drought treatments of HSP70 gene family in soybean (Glycine max L.) - Zhang, Ling; Zhao, Hong-kun; Dong, Qi-li; Zhang, Yuan-yu; Wang, Yu-min; Li, Hai-yun; Xing, Guo-jie; Li, Qi-yun; Dong, Ying-shan (Frontiers in Plant Science, 2015)
Heat shock proteins (HSPs) perform a fundamental role in protecting plants against abiotic stresses. Previous studies have made great efforts in the functional analysis of individual family members, but there has not yet been an overall analysis or expression profiling of the HSP70 gene family in soybeans (Glycine max L.). In this study, an investigation of the soybean genome revealed 61 putative HSP70 genes, which were evaluated. These genes were classified into eight sub-families, denoted I-VIII, based on a phylogenetic analysis. In each sub-family, the constituent parts of the gene structure and motif were relatively conserved. These GmHSP70 genes were distributed unequally on 17 of the 20 chromosomes. The analysis of the expression profiles showed that 53 of the 61 GmHSP70 genes were differentially expressed across the 14 tissues. However, most of the GmHSP70s were differentially expressed in a tissue-specific expression pattern. Furthermore, the expression of some of the duplicate genes was partially redundant, while others showed functional diversity. The quantitative real-time PCR (qRT-PCR) analysis of the 61 soybean HSP70 genes confirmed their stress-inducible expression patterns under both drought and heat stress. These findings provide a thorough overview of the evolution and modification of the GmHSP70 gene family, which will help to determine the functional characteristics of the HSP70 genes in soybean growth and development.